Fitness - Kedgem Joanna; Watson, Joanna (Chicago, USA Raintree, 2005)
This book tells you all about fitness. It explains why it is important to exercise regularly and how exercise can boost your confidence. It examines the positive effects good fitness can have on your body and your mind. Facts are explained clearly and advice is given by professionals
The World around us (Human Body)
Keywords: Human Body